Phytic acid assisted ultra-fast in situ construction of Ni foam-supported amorphous Ni–Fe phytates to enhance catalytic performance for the oxygen evolution reaction. Issue 14 (15th June 2022) - Gao, Taotao; Wu, Shuaiwei; Li, Xiaoqin; Lin, Chaohong; Yue, Qu; Tang, Xiangmin; Yu, Shumin; Xiao, Dan
Abstract : A phytic acid-induced etching and complexation growth strategy is used to fastly prepare the amorphous bimetallic Ni–Fe phytate with a cross-linked structure on nickel foam, which shows efficient catalytic activity and robust stability for OER. Abstract : For the efficient and low-cost utilization of clean energy sources, the preparation of robust catalytic electrodes for the oxygen evolution reaction (OER, the key half-reaction in new energy conversion and storage systems) via a simple and time-saving preparation strategy is important. In this work, bimetallic Ni–Fe phytates are rapidly in situ grown on the surface of nickel foam (Ni–Fe-phy@NF) based on the robust complexation ability of the phytate ion. The phytate ion with multiple complexation sites promotes the formation of large cross-linking networks, which enhances the synergistic effect between Ni, Fe and P and the interaction between active materials and the nickel foam substrate. Besides, the partial dissolution of the phosphorus in the cross-linking networks induces the formation of abound porous structures during the OER process. This process is accompanied by the transformation from metal phytates to amorphous Ni–Fe-based oxides and hydroxides with a high valence state as efficient active sites for the OER. Therefore, the Ni–Fe-phy@NF electrode shows robust OER catalytic activity and enduring stability. Note that the synthetic strategy based on ligands with multiple complexation sites can be further used to rapidly design and prepare other novel three-dimensional electrode materials with improved catalytic performance.